Comparison of profile and short-term outcome of acute kidney injury between steroid sensitive and steroid resistant nephrotic syndrome - Uma Maheshwari M.; Alpana Ohri; Amish Udani; Chintan Shah (International Journal of Contemporary Pediatrics, 2023)
Background: Acute kidney injury (AKI), a severe complication of nephrotic syndrome (NS) is being more prevalent in recent times. Objectives were: 1) Determine incidence, etiology, short term outcome of AKI in children hospitalised with NS. 2) Compare above variables in steroid sensitive nephrotic syndrome (SSNS) versus steroid resistant nephrotic syndrome (SRNS). Methods: Prospective observational study over 18 months including all consecutive nephrotics hospitalized with AKI. AKI defined according to KDIGO criteria with baseline creatinine taken as lowest value in last 6 months/ nadir during stay. Secondary NS were excluded. Demographics, clinical features, labs, hospital course, treatment and follow up at 3 months were recorded. SSNS and SRNS were compared. Results: The incidence of AKI in hospitalised nephrotics (30/304) was 9.8%, 30 patients (16 boys) with mean age 4.08 years (± 4.04 SD). Common etiologies of AKI were infection (60%), nephrotoxic drugs, hypovolemia, and thrombosis in decreasing order. Nephrotics developing AKI had a longer hospital stay versus those without AKI (p<0.001). The 2/30 patients died (6%), 10/30 (33.3%) required PICU, 7/30 (26%) needed RRT. Among discharged patients 4/28(14.28%) had persistent deranged renal functions at 3 months follow up, all of whom belonged to SRNS category. Comparison of 14 patients in SSNS with 16 in SRNS showed UTI (31.3%), drugs (25%), systemic infection (31.3%), thrombosis (12.5%) as etiologies in SRNS. Systemic infection (42.9%), drugs (21.4%), UTI (14.3%) and hypovolemia (21.4%) were causes in SSNS. Mortality rate, need for PICU (p=1.0), RRT (p=1.0) was similar (6%,37.5%, 25%) Vs (7%,28.5%, 21.4%). Conclusions: AKI is seen in up to a tenth of children with NS equally in SSNS and SRNS. While etiology and severity of AKI in the 2 groups is similar, short-term outcome in SRNS is more ominous.